Accuracy of equilibrium magnetization mapping in sliced two‐dimensional spoiled gradient‐recalled echo pulse sequence with variable flip angle. Issue 5 (6th February 2013) - Kuribayashi, Hideto; Sekino, Masaki; Minowa, Takuya; Maitani, Yoshie; Ohsaki, Hiroyuki; Tsushima, Shohji; Hirai, Shuichiro; Ueda, Masayuki; Katayama, Yasuo
<x xml:space="preserve">Abstract</x> Purpose To evaluate the accuracy of an equilibrium magnetization (M0) map obtained using a two‐dimensional (2D) spoiled gradient‐recalled echo (SPGR) pulse sequence with variable flip angle (VFA). Materials and Methods Single‐slice 2D SPGR images of 4% agar gel phantoms with different gadolinium‐diethylene triamine pentaacetic acid (Gd‐DTPA) concentrations (0–1 mM) were obtained with a VFA (2–30°). The 2D SPGR‐VFA data were acquired with different repetition times (TRs; 7.8–117.2 ms), Gaussian and sinc RF pulses, and different field strengths (4.7, 7, and 9.4 Tesla). M0 and T1 maps were calculated from the 2D SPGR‐VFA data. M0 and T1 values were compared with those calculated from free‐relaxed 2D gradient‐recalled echo (GRE) images and inversion recovery‐prepared 2D SPGR images. The M0 and T1 slice profiles were also investigated. Results Consistent M0 values were obtained, regardless of the different Gd concentrations, TRs, and pulse sequences. The M0 slice profiles calculated from the sliced SPGR‐VFA data quantitatively reproduced those calculated from the free‐relaxed sliced GRE. In contrast, the T1 values calculated from the 2D SPGR‐VFA data were underestimated at a high Gd concentration, short TR, and Gaussian RF pulse. Conclusion M0 values calculated from 2D SPGR‐VFA images are highly quantitative. J. Magn. Reson. Imaging 2013;38:1245–1250. © 2013 Wiley Periodicals, Inc.